Clinical outcomes of platinum-based chemotherapy in patients with advanced breast cancer: An 11-year single institutional experience. (June 2021) - Franzoi, Maria Alice; Saúde-Conde, Rita; Ferreira, Sofia Cristóvão; Eiger, Daniel; Awada, Ahmad; de Azambuja, Evandro
Abstract: Background/methods: Although the prognosis of metastatic breast cancer (BC) has improved, some patients still develop high burden metastases or visceral crisis (VC) and polychemotherapy is commonly used in these cases. Data reporting the real effectiveness of this strategy are scanty. Therefore, the outcomes of patients with metastatic BC treated with platinum-based chemotherapy (P-ChT) at the Jules Bordet Institute during the period of January 2008 and December 2018 were retrospectively reviewed. The presence of VC was defined according to ABC 4 criteria. Results: 441 patients were identified: visceral metastases were observed in 430 (97.5%) while 261 (59.2%) presented VC. As for metastatic BC subtype, 255 (57.8%) had ER-positive/HER2-negative, 41 (9.3%) ER-positive/HER2-positive, 34 (7.7%) ER-negative/HER2-positive and 111 (25.1%) triple-negative BC. Median number of prior treatment lines was 3.8 (0–12). Median OS with P-ChT in the entire cohort was 6.13 months. Patients with VC had lower OS than patients without VC (8.6 vs 3.7 months; p < 0.001). On multivariate analysis, the variables correlated with worse OS were hyperbilirubinemia (HR 1.90; 95% CI 1.34–2.75), ECOG ≥2 (HR 1.77; 95% CI 1.13–2.78) and ECOG ≥3 (HR 2.52; 95% CI 1.48–4.28), and >3 previous treatment lines (HR 2.27; 95% CI 1.53–3.21). Of the 261 patients with VC, 106 (40.5%) presented a resolution of the VC which correlated with better OS (9.3 vs 2.0 months, HR 0.27; 95% CI 0.21–0.36). Conclusion: Patients who overcome VC benefit from P-ChT with OS similar to patients without VC. In this analysis, hyperbilirubinemia, poor ECOG and >3 previous treatment lines were significant prognostic factors in the overall study population. Highlights: Outcomes of pts with advanced BC treated with platinum-based chemotherapy at our Institution were reviewed. Our results highlight the poor prognosis of pts with BC and visceral crisis (VC). Hyperbilirubinemia, poor ECOG PS, and >3 prior treatment lines may be factors associated with inferior OS. Prospective studies in pts with VC are needed to provide better guidance towards treatment decisions.